Performance determining factors in elite sprinters during sprint start and two following successive supports - Debaere, S.; Jonkers, I.; Aerenhouts, D.; Hagman, F.; Gheluwe, B.; Delecluse, C. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
Sprint start out of the blocks and successive acceleration are technically challenging as the athlete goes from a bended to a forward leaning position. Therefore, the body center of mass (COM) has to be accelerated forward and upwards. Optimal sprinting performance relies on attaining maximal forward acceleration. However, adequate vertical acceleration must be generated to reach sufficient height to prepare for the following step (Weyand, 2000). Horizontal acceleration is mainly determined by the horizontal ground reaction force that will affect sprint velocity and therefore final sprint performance (Mero, 1988). Kinematics and kinetics of the start action and maximal sprinting were intensively studied; however little is known on the transition from the set position to the running position during the first two strides. This study aims to identify the factors in the start action as well as in the first and second contact after block clearance that determine sprinting performance in terms of speed and acceleration.